Queen Christina [videorecording (DVD)] - Garbo, Greta, 1905-1990; Gilbert, John, 1897-1936; Keith, Ian, 1899-1960; Stone, Lewis, 1879-1953 (Archive collection., 2019)
Portrayal of the 17th century Queen of Sweden who relinquishes her throne for her lover, the ambassador from Spain.